SECOND POSTCOMMUNIST REVOLUTION IN UKRAINE - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The author analyzed events in Ukraine in the period November 2013 – February 2014. Defining them as a political revolution, he reveals its causes, characterizes stages. Based on the comparative analysis of revolutions that have occurred in the postcommunist space, he reveals its specificity. Foreign factor of political development have been given special attention.